Control of suddenly expanded flows with micro-jets - Khan, Sher Afghan; Rathakrishnan, E. (Walter de Gruyter, 2003)
The results of an experimental investigation carried out to control the base pressure in a suddenly expanded axi-symmetric passage are presented in this paper. Active control in the form of micro-jets was employed to control the base pressure. Air injection at four locations at the base, symmetric to the nozzle axis was used as the active control. The jet Mach numbers at the entry to the suddenly expanded duct, studied were 1.87, 2.2 and 2.58. The length-to-diameter ratio of the suddenly expanded duct was varied from 10 to 1. Nozzles generating the above jet Mach numbers were operated with nozzle pressure ratio (NPR) in the range 3 to 11. In addition to base pressure, wall pressure field along the enlarged duct length was also studied. It is found that the active control in the form of blowing through small orifices (micro-jets) are effective in controlling the base pressure field. As high as 95 per cent increase in base pressure was achieved for certain combination of parameters of the present study. From the present investigation it is evident that for a given Mach number and NPR one can identify the L/D which will result in maximum increase/decrease of base pressure.